Tourism In Belize : Ensuring Sustained Growth - Chow, Julian (IMF Working Papers; Working Paper ;, 2019)
Belize's tourism sector has witnessed impressive growth in recent years with overnight tourist arrivals registering double digit annual growth rates since 2016. To guide the development of the tourism sector from 2012 to 2030, the government endorsed a National Sustainable Tourism Master Plan in 2011, setting various initiatives and targets for the immediate and medium terms. Using a panel regression analysis on twelve Caribbean countries, this paper finds that accelerating structural reforms, fortifying governance frameworks, reducing crime, and mitigating the impact of natural disasters will help sustain tourism growth in Belize and contribute to economic well-being. This is in addition to tackling infrastructure bottlenecks and mitigating concerns relating to the 'shared economy'.